Frontal Face Detection using Haar Wavelet Coefficients and Local Histogram Correlation - Iwan Setyawan; Ivanna K. Timotius; Andreas A. Febrianto (LPPM ITB, 2011)
Face detection is the main building block on which all automatic systems dealing with human faces is built. For example, a face recognition system must rely on face detection to process an input image and determine which areas contain human faces. These areas then become the input for the face recognition system for further processing. This paper presents a face detection system designed to detect frontal faces. The system uses Haar wavelet coefficients and local histogram correlation as differentiating features. Our proposed system is trained using 100 training images. Our experiments show that the proposed system performed well during testing, achieving a detection rate of 91.5%.